CRREL report. - Cold Regions Research and Engineering Laboratory (U.S.)
Some no. issued in 2 or more parts; no. 12 issued semiannually 1951-56 and annually thereafter, retaining title SIPRE through its 1961 vol. Mode of access: Internet. No. for 1950-1961 issued by the Laboratory under an earlier name: U.S. Army. Snow, Ice and Permafrost Research Establishment. Microfiche copy: Microfiche. [Washington, DC], Suptdocs/GPO. microfiches. negative. 11 x 15 cm.